Blind spots obscure understanding of how forests affect human health - Rosenstock, T.S.; Rowland, D.; Liew, Z.; Hickson, K.; Zeitler, L.; McMullin, S.; Jamnadass, R.; Ickowitz, A. (Elsevier, 2023)
Health crises have raised awareness of the links between forests and human health. For example, outbreaks of Ebola virus and hypotheses about the origins of SARS-CoV-2 have highlighted the risk of zoonotic spillover events from forest-dwelling animals.1, 2 Likewise, forest fires in Australia (2019–20), the Amazon rainforest (2019), and southeast Asia (2015) have drawn attention to the respiratory health effects on populations exposed to smoke and haze.3 Other links between forests and health, such as the role of forests in mitigating natural disasters4 and regulating infectious disease vectors,5 are well established but less well known outside the scientific community. For example, the loss of coastal mangroves exacerbated morbidity and mortality following the 2004 Indian Ocean earthquake and tsunami,6 and forest loss amplified the effects of the 2021 flooding across Europe,7 contributing to injury, increased prevalence of waterborne diseases, and death.